Hydration Status of Expatriate Manual Workers During Summer in the Middle East - Bates, Graham; Miller, Veronica; Joubert, D. (Oxford University Press, 2010)
Background: Implicit in all indices used for risk assessment in the prevention of heat stress is the assumption that workers are healthy and well hydrated; studies in Australian mine workers have shown that this is not the case. Where workers are poorly hydrated, the level of protection offered by management strategies based primarily on environmental monitoring is compromised. Objectives: To investigate the hydration status of expatriate workers during summer in a range of work environments in the Middle East as large numbers of expatriate workers are employed as manual labourers in construction and other industries under extreme heat stress conditions where heat illness is a significant concern. The aim was to ascertain whether the generally inadequate hydration status, previously documented in Australian workers, is also an issue in these workers and make practical recommendations for control. Methods: Studies were carried out at four sites to document the hydration status of exposed workers in different workplaces using urine specific gravity at three time points over two different work shifts. Results: Although the workers were found in general to be better hydrated than their Australian counterparts, a high proportion were still found to be inadequately hydrated both on presentation for work and throughout the shift. Hydration status did not alter greatly over the course of the day at individual or group level. Conclusions: Interventions are required to ensure that workers in extreme heat stress conditions maintain adequate levels of hydration. Failure to do so reduces the protection afforded by heat stress indices based on environmental monitoring.